Deadlocked in history and geopolitics: Revisiting Armenia–Turkey relations. (21st August 2021) - Ter‐Matevosyan, Vahram
Abstract: Located at the crossroads of Europe and Asia, Armenia and Turkey are two neighboring countries that share a 311 km of land border. Official relations between them, however, remain antagonistic as they never established diplomatic relations, and the land border remains closed. All the past efforts to normalize relations and eradicate the standoff have foundered. This article engages with several methodological problems and (mis)perceptions that persist in existing interpretations of Armenia–Turkey relations and examines their impact on the current deadlock. It particularly discusses the questions of the closed border, its relevance to the conflict in Karabakh, the importance of disentangling the process of normalization from reconciliation, and its impact on past normalization initiatives. The article argues that critical rethinking of several deep seated conceptions and approaches could expand our understanding about the roots of the present rift and propose avenues for resolving the impasse.